1984
DOI: 10.1084/jem.160.4.1001
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal administration of idiotype or antiidiotype primes for protection against Escherichia coli K13 infection in mice.

Abstract: Antibodies directed against the capsular polysaccharides (Ps) of encapsulated pathogenic bacteria can protect the host against infection with such organisms. The immune response to Ps, however, does not develop until relatively late in ontogeny. We have, therefore, studied alternative ways to stimulate anti-Ps antibody responses in neonates, namely priming with idiotype (Id) and anti-Id. We believe that these studies provide the first demonstration of the use of an anti-Id antibody to prime for protection agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
84
1

Year Published

1989
1989
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(91 citation statements)
references
References 24 publications
6
84
1
Order By: Relevance
“…This early report represents an example of an anti-idiotypic MAb priming for a protective immune response against a non-protein antigen (12). Although our current trial is the first attempt to use an anti-idiotypic MAb vaccine to prime for a response against the original antigen in patients, we found no evidence of priming by BEC2.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…This early report represents an example of an anti-idiotypic MAb priming for a protective immune response against a non-protein antigen (12). Although our current trial is the first attempt to use an anti-idiotypic MAb vaccine to prime for a response against the original antigen in patients, we found no evidence of priming by BEC2.…”
Section: Discussioncontrasting
confidence: 50%
“…Also, we wished to test the hypothesis that the antiidiotypic MAb BEC2 could prime the host for response to the GD3-L-KLH vaccine. This has been observed in a mouse model against the antigen Escherichia coli polysaccharide (12). In this current trial, melanoma patients who were free of disease but at high risk for recurrence were immunized either with BEC2/ BCG followed by GD3-L-KLH/QS-21 or GD3-L-KLH/QS-21 followed by BEC2/BCG.…”
Section: Introductionmentioning
confidence: 99%
“…After the first demonstration that the antigenic functions of carbohydrates can be mimicked by anti-idiotypic Abs (24), murine mAbs have been successfully used as experimental anti-idiotypic vaccines to induce protective immunity against different encapsulated bacteria (13)(14)(15)25). More recently, short peptides also proved capable of mimicking carbohydrate Ags (12,26,27).…”
Section: Discussionmentioning
confidence: 99%
“…12). The ability of murine monoclonal anti-idiotypic Abs to function as surrogate vaccines against several different encapsulated pathogens has been shown in the past (13)(14)(15). More recently, it was shown that anti-idiotypic single-chain Ab fragments (scFv) are sufficient to induce protective, capsulespecific Ab responses (16).…”
mentioning
confidence: 99%
“…A number of anti-idiotype vaccines have been developed in animal models and the induction of neutralizing levels of antibody and cell-mediated immunity have been demonstrated (1, 8,13,17). Thus, anti-idiotype vacccines have been used to induce protective immunity against viruses (2, 3, 9-11, 15, 17, 21), bacteria (12,18,19), and parasites (4, 16) and they have also been used effectively in cancer therapy (5).…”
mentioning
confidence: 99%